Rickettsialpox: practical aspects of diagnosis and treatment - O. N. Domashenko; D. S. Panieva; V. A. Gridasov (Журнал инфектологии, 2020)
The objective: to study the clinical course of rickettsialpox at the current stage in the Donetsk city.Materials and methods. 43 patients (men – 26, women – 17) aged 17–42 years (M ± 29) years were examined. Verification of the diagnosis was based on the results of ELISA (IgM) with R.Akari in titer 1: 160 in 9, 1: 320 in 15 patients.Results. The observed cases of rickettsialpox were sporadic. All patients were residents of Donetsk city. The presence of rodents in places of living or work was indicated by 39,5% of patients. The clear seasonality of rickettsialpox drew attention: 59% of patients were hospitalized in June, 7% in August. Uniform distribution of hospitalization in July, September and October was observed (14%, 14%, 12%, respectively). Acute onset of the disease was noted in 53,5% of patients. 16,3% revealed a large papule under the crustduring initial examination, which is defined as the primary element. Fever accompanied by chills was observed in 93.0% of patients from the first day of the disease. The duration of the fever was (11,4 ± 1,2) days. The rash appeared in the first four days of the disease, papulo-vesicular elements predominated (60.5%). Leukopenia (3,9 ± 0,9×109 G/L) was observed in the blood with a shift to the left (14,8 ± 1,3)% and lymphocytosis (49,3 ± 1,6)%, ESR – (21 ± 0,9) mm/h. Medium-severe course was observed in 55.8%, severe – 39,5%, mild – in 4,7% of patients. Doxycycline was prescribed asetiotropic therapy.Conclusion. Rickettsialpox is an endemic disease for the Donetsk city. Data on the true spread of the disease are not available. Undetectable primary affect and regional lymphadenitis in most patients is the reason for the unjustified exclusion of the disease.  Laboratory diagnosis questions seem relevant for studying the problem of rickettsialpox.